Relationship Between Ball Speed and Spin in Elite Youth Table Tennis Players Using Optical Sensors - Thibault Delumeau; Christophe Plot; Eric Le Carpentier; Thibault Deschamps; Pierre Mousseau (Applied Sciences)
This paper investigates the relationship between ball spin and linear speed in table tennis. This study uses a simple photodiode montage to introduce a methodology for measuring spin based on light reflection on the ball’s surface. Two optical-based measurement systems were developed to measure either the ball’s speed or spin. This paper describes sensor calibration and error estimation. Those systems measured ball kinetic parameters from nine young elite players (aged 15 ± 1.5 years) who volunteered to perform 4 exercises. Results showed a strong positive linear relationship between the ball’s speed and spin (r = 0.96, R2 = 0.93, p < 0.001). The effect of exercise conditions on ball speed has been studied using a statistical test, ANOVA. Results showed a significant main effect of exercise conditions on ball speed (p < 0.05) with a very large effect size (η2 = 0.82). The study revealed significant variations in linear speed based on the type of stroke (backhand, forehand) and the incoming ball’s spin (topspin, backspin), with topspin forehand strokes achieving higher speeds compared to backhand strokes. These findings provide valuable knowledge for players to enhance performance in a competitive environment.